2012
DOI: 10.1007/bf03379590
|View full text |Cite
|
Sign up to set email alerts
|

Hostility and Anger in Patients Dependent on Different Psychoactive Drugs

Abstract: We assessed 311

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This is consistent with findings of Sharma et al [10] and Agha Yusefi et al [16] Ilyuk et al [20] in their study also showed that in all groups of drug and alcohol-dependent participants, anger was significantly higher. Quinn et al [21] also stated that adolescents with high trait anger exhibit higher substance abuse.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with findings of Sharma et al [10] and Agha Yusefi et al [16] Ilyuk et al [20] in their study also showed that in all groups of drug and alcohol-dependent participants, anger was significantly higher. Quinn et al [21] also stated that adolescents with high trait anger exhibit higher substance abuse.…”
Section: Discussionsupporting
confidence: 92%
“…AD individuals, compared with the control group, obtain significantly higher scores on the psychoticism scale ( Chadhury, Das & Ukil, 2006 ). Moreover, AD individuals more frequently experience hostility, irritability, and aggression (both verbal and nonverbal) in comparison with the healthy population ( Ilyuk et al, 2012 ). Endler, Parker & Butcher (2003) found a positive association between an emotion-oriented coping style and various measures of psychopathology in the MMPI-2 scale, including depression, anxiety, obsessiveness, anger, and low self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Higher level of aggressiveness, anger and irritation were in groups of polysubstance and stimulant abusers. The researchers found specific predictors of anger and aggression for groups of subjects dependent on different drugs [23]. In a different study conducted among 200 participants that involved three juvenile schools in Malaysia found a significant correlation between those who have been using heroin and morphine with aggressive behavior.…”
Section: Introductionmentioning
confidence: 98%